An Analysis Of Gadget Addiction Phenomenon Among Teenager Of Bajo Tribe In Parumaan Village - Sundari Sundari; Nur Syamsiyah Ekhsan; Yanto Yanto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study analyze the gadget addiction phenomenon among teenager of bajo tribe in Parumaan village to determine the gadget addiction phenomenon among teenager of Bajo tribe in Parumaan village and to determine the impact of gadgets addiction of teenagers Bajo Tribe in Parumaan village, Alok Timur district, Sikka regency. the data method of this research uses qualitative descriptive conducted by teenager of the Bajo tribe in the Parumaan village, the data sources in this study are the teenagers of the Bajo tribe in the Parumaan village, namely junior high school students ranging from 13 to 15 years old, the data collection technique in this study is in the form of direct documentation and interviews, the results of this study are: 1. gadget addiction phenomenon among teenager of Bajo tribe in parumaan village, based on the results of careful interviews that Bajo teenagers in Parumaan village use gadgets every day, there are 7 teenagers who use gadgets at the same time for 15 hours, 3 people for 13 hours, 2 people for 16 hours, 2 people for 14 hours and 1 person for 12 hours. teenagers of the Bajo tribe in Parumaan village use gadgets to play Whatsapp, Facebook, Youtube, Instagram, Tiktok, Video Snacks and also Twitter. 2. the impact of gadgets addiction of teenagers Bajo tribe in Parumaan village, efect on learning achievement decrease  use of gadgets will have a negative impact, such as the learning process does not run perfectly. This condition is due to the technology in these gadgets being able to be used by Bajo Tribe teenager in Parumaan Village to access various information, especially information related to subjects, less interaction with others here are many negative impacts of using gadgets, one of which is causing a decrease in social skills. Teenagers of the Bajo Tribe in Parumaan Village become busy and focused on their gadget screens so they no longer care about their surroundings and no longer understand the ethics of socializing, Impact on health Information and entertainment. They can open Youtube to view videos, play Games, scroll on Tiktok, watch Snack videos, WhatsApp and Instagram.It is not surprising then that students feel at home staring at gadget screens for long, study less teenagers of the Bajo tribe in Parumaan village are more lazy to think, because the gadgets they play are easier or simpler than having to draw and so on. So teenagers will do the easy things, don't want strenuous activities, such as studying, drawing, or writing.